2002
DOI: 10.1002/cncr.10906
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator‐activated receptor γ ligand troglitazone induces cell cycle arrest and apoptosis of hepatocellular carcinoma cell lines

Abstract: BACKGROUND Ligand activation of peroxisome proliferator‐activated receptor γ (PPARγ) results in the inhibition of proliferation of various cancer cells. The aim of this study is to investigate the mechanisms of cell growth inhibition of hepatocellular carcinoma (HCC) cell lines by the PPARγ ligand, troglitazone. METHODS Six HCC cell lines were used to study the effects of troglitazone on cell growth by 3‐[4,5‐dimethylthiazol‐2‐yl]‐2,5‐diphenyltetrazolium bromide (MTT) assay, on cell cycle by flow cytometry, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
54
1
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 30 publications
(48 reference statements)
4
54
1
3
Order By: Relevance
“…In addition, a novel function of PPAR␥ in tumor pathogenesis has been reported recently, which includes PPAR␥ ligand-dependent growth inhibition and/or apoptosis in a variety of human cancer cells (2,(11)(12)(13). Several studies have demonstrated that induction of apoptosis was accompanied by the up-regulation of several pro-apoptotic genes, Bax and caspase-3 and -9, and down-regulation of the anti-apoptotic gene Bcl-2 (47,48), suggesting that transactivation of PPAR␥ is likely to regulate expression of apoptosis modulators at the transcriptional level and contribute as an important modulator of tumor suppression. In this study we demonstrated that the trans-activation function of PPAR␥ was up-regulated by mutation of Lys-107, the major target for sumoylation in PPAR␥.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a novel function of PPAR␥ in tumor pathogenesis has been reported recently, which includes PPAR␥ ligand-dependent growth inhibition and/or apoptosis in a variety of human cancer cells (2,(11)(12)(13). Several studies have demonstrated that induction of apoptosis was accompanied by the up-regulation of several pro-apoptotic genes, Bax and caspase-3 and -9, and down-regulation of the anti-apoptotic gene Bcl-2 (47,48), suggesting that transactivation of PPAR␥ is likely to regulate expression of apoptosis modulators at the transcriptional level and contribute as an important modulator of tumor suppression. In this study we demonstrated that the trans-activation function of PPAR␥ was up-regulated by mutation of Lys-107, the major target for sumoylation in PPAR␥.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that troglitazone (TRO), a synthetic PPARg ligand, causes growth inhibition, induces differentiation, and triggers apoptosis of various human malignant cells (Asou et al, 1999;Clay et al, 1999;Demetri et al, 1999;Sugimura et al, 1999;Hisatake et al, 2000;Rumi et al, 2001;Takashima et al, 2001;Begum et al, 2002;Yoshizawa et al, 2002). TRO inhibits proliferation of MCF-7 breast cancer cells by inducing cell cycle arrest and causing apoptosis (Yin et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Each of the subtypes forms a heterodimeric complex with the retinoid X receptor and then binds to the PPAR response element (PPRE). This interaction can regulate cellular differentiation (4), apoptosis (5,6), inflammatory response (7,8), and lipid metabolism (9).…”
mentioning
confidence: 99%